2014
DOI: 10.1159/000366018
|View full text |Cite
|
Sign up to set email alerts
|

Visual Selective Attention Is Impaired in Children Prenatally Exposed to Opioid Agonist Medication

Abstract: Aims: To examine whether prenatal exposure to opioid agonist medication is associated with visual selective attention and general attention problems in early childhood. Method: Twenty-two children (mean age = 52.17 months, SD = 1.81) prenatally exposed to methadone, 9 children (mean age = 52.41 months, SD = 1.42) prenatally exposed to buprenorphine and 25 nonexposed comparison children (mean age = 51.44 months, SD = 1.31) were tested. Visual selective attention was measured with a Tobii 1750 Eye Tracker using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 38 publications
(63 reference statements)
0
25
0
Order By: Relevance
“…One found no significant difference in visual selective attention among 31 children of mothers treated with BUP versus MET 40. The second study found significantly prolonged visual latency in 22 infants of MET‐treated mothers compared with 30 infants of BUP‐treated mothers 49.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…One found no significant difference in visual selective attention among 31 children of mothers treated with BUP versus MET 40. The second study found significantly prolonged visual latency in 22 infants of MET‐treated mothers compared with 30 infants of BUP‐treated mothers 49.…”
Section: Resultsmentioning
confidence: 94%
“…Of 1111 citations identified, 140 full‐text papers were assessed for eligibility, and 18 studies 18, 19, 20, 21, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 (reported in 23 papers 18, 19, 20, 21, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52) satisfied our inclusion criteria (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is one of several based on the cohort Konijnenberg & Melinder, 2015;Lund et al, 2012;Melinder et al, 2013;Sarfi, Smith, Waal, & Sundet, 2011;Sarfi et al, 2013). While not all mothers participated in interviews at the 4-year follow up, this is not likely to affect the representativeness of the sample, as described in a previous study on the cohort (Lund et al, 2014).…”
Section: Methodsmentioning
confidence: 99%